THE REPRESENTATION OF MULTIPLE INTELLIGENCES IN THE PRIMARY SCHOOL ENGLISH TEXTBOOKS MY NEXT WORDS: A CONTENT ANALYSIS - Martins, Luvita Freitas; Mukarto, F. X. (Universitas Muhammadiyah Metro, 2024)
Each student has individual differences, including intelligence profiles, that teachers must consider. The recent curriculum, Kurikulum Merdeka, emphasizes the freedom for the teacher to plan the lesson based on students’ needs and abilities. Since teachers widely use textbooks as a source and guidance to conduct an appropriate teaching-learning process, it is essential to have textbooks that accommodate students’ multiple intelligences. This study aimed to determine the representation of Multiple Intelligences in primary school textbooks titled My Next Words. This study used content analysis as the research method. Eight units were chosen, with two randomly selected from each of the four textbooks. The data were gathered by administering a coding sheet and analyzed by calculating the frequency of occurrence. The results indicated that My Next Words textbooks accommodate all types of intelligences to a certain degree. The most frequently occurring types of intelligence are verbal/linguistic and visual/spatial intelligence. This study can serve as a source for teachers to recognize and address various intelligences, helping them to adapt their teaching material. Besides, it can inform textbook developers to enhance the content of textbooks to provide more diverse material that caters to different intelligences.